Estágio supervisionado obrigatório tumor mamário canino: relato de caso - Nogueira, Isadora Cristina de Souza (Universidade Federal Rural do Semi-Árido, 2021)
The present work consists of a report of the activities developed during the obligatory supervised internship, carried out at the Veterinary Center of Mossoró. The internship provides students with practical experiences associated with the knowledge base acquired during graduation, improving their professional conduct. During the internship, clinical and surgical care of dogs and cats were followed, and the case of a female dog diagnosed with breast tumor was selected for the elaboration of a report. The patient consisted of a 15-year-old female, castrated poodle, weighing 6,400 kg, with a history of nodules in the breast region. After performing the anamnesis and physical examination, the diagnosis of a breast tumor in the left cranial thoracic breast and left caudal abdominal breast was established, and with that, complementary imaging tests were requested to verify metastasis conditions; chest X-ray and abdominal ultrasound showed results not compatible with metastasis, and surgical therapy with mastectomy was chosen. In view of the pre-surgical exams, the animal was considered able to perform the procedure. We proceeded with unilateral mastectomy associated with lipoma excision. In this context, tumors present in the cranial thoracic breast and caudal abdominal breast were removed and sent for histopathological analysis. The result of the histopathological analysis confirmed the histological type of tubulopapillary carcinoma. Thus, we can infer that breast tumors correspond to a high frequency neoplasm in bitches, with a higher incidence in geriatric animals, in which the increased life expectancy of dogs and cats has provided a higher percentage of diagnosis of this disease.
Keywords: Mastectomia; Mamário; Metástase; Tumor; CIENCIAS AGRARIAS::MEDICINA VETERINARIA